(untitled) (Innovative professional education, 2025)
The article is devoted to the study of the phenomenon of professional competence of general education teachers. The paper examines the essential characteristics of professional competence, its structure, and development features. The significance of general education training for skilled workers is justified by the necessity of possessing natural-mathematical and socio-economic knowledge, the ability to apply digital technologies, and the skills to effectively solve complex production-related problems